Asymptotic representations of solutions of essentially nonlinear systems of ordinary differential equations with regularly and rapidly varying nonlinearities - Evtukhov, V. M.; Shlepakov, O. R. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain asymptotic representations for one class of solutions of systems of ordinary differential equations more generalthan systems of the Emden – Fowler type.